Pengaruh Upah Minimum Dan Tingkat Partisipasi Angkatan Kerja Terhadap Tingkat Pengangguran Terbuka Di Jawa Timur Periode 2018-2022 - Saukina Ila Salsabila; Suhaeda Nabila; Risma Ayu Rianti; Dhimas Priyoga; Agus Eko Sujianto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to determine the effect of minimum wages and labor force participation on open unemployment in East Java Province 2018-2022. The dense population makes Indonesia face economic problems such as open unemployment. This happens because the number of job seekers is not balanced with the number of jobs available. The level of open unemployment occurs in every region, especially in East Java Province. Based on BPS data for the 2018-2022 period, East Java Province experienced an increase in open unemployment in 2020 with a percentage of 5.84%. The research method used uses a quantitative descriptive model approach with combined data between time series and cross-sections. The analytical method used in this research is the multiple regression test method, panel data model which is processed using SPSS version 26. The data collection technique is taken from secondary data from BPS East Java Province in 38 regions. The research results show that the influence of minimum wage instruments and labor force participation on open unemployment in East Java Province can be seen from the statistical probability values of the t test and f test. The results of the t test showed that the minimum wage instrument (X1) had a significant effect on the open unemployment rate (Y) in East Java Province. Meanwhile, the labor force participation instrument (X2) does not show a significant influence on the open unemployment rate (Y) in East Java Province. Meanwhile, the results of the f test research show that the two instruments (X1 and X2) simultaneously have a significant influence on the open unemployment rate (Y) in East Java Province.